Trends in Brain Cancer-Associated Mortality Among South African Men and Women - Yoshan Moodley; Samson Mashele (Universitas Airlangga, 2026)
Highlight: Mortality from brain cancer is generally much higher in South Africa when compared with other countries. Brain cancer mortality has declined among South African men and increased among South African women. ABSTRACT Introduction: South Africa has seen a general increase in cancer burden. Mortality from brain cancer has yet to be studied, which is significant given the poor prognosis associated with this condition. Objective: The objective of this study was to report on the trends in mortality for brain cancer among South African men and women. Methods: This was a descriptive trends analysis of South African national mortality data for the period 2007-2016. The mortality dataset contains information on all reported deaths in South Africa, including deaths associated with brain cancer, and is based on the International Classification of Diseases Coding,10th Revision (ICD-10). A descriptive analysis was conducted to calculate the annual age-specific and age-standardized rates of brain cancer-associated mortality, which were then plotted separately for each gender. Results: There were 4,110 brain cancer-associated deaths included in this study. Mortality fluctuated across the study period but was mostly higher in the older age groups. Age-standardized mortality rates in men ranged from 4.26-4.63 per 100,000 population and declined at the end of the study period. Age-standardized mortality rates in women ranged from 2.34-2.62 per 100,000 population and increased at the end of the study period. Conclusion: The elderly and men had the highest rates of brain cancer-associated mortality, although a declining trend was noted in the latter. Brain cancer-associated mortality is increasing among women. There is an urgent need for improved brain cancer control in South Africa.